A quantitive analysis of the impact of the economic crisis in the press industry and an appraisal of the development of Information Society in Europe - Larrañaga Rubio, Julio (Estudios sobre el Mensaje Periodístico, 2012)
Internet has worsened the sale drops of printed press and has also reduced revenues from announcements. This paper furnishes a statistical analysis of the actual relationship between sales drops in the printed press and the development of Information Society in several European countries. It also focuses on the statistical relationship between the drops in printed press and the percentage of its readers online
Keywords: Press industry; Information Society; online press; printed press; Web 2.0.